Makna Jihad Habib Ja’far sebagai Kontra Narasi Ekstremisme Keagamaan (Analisis Podcast “Login” Close the Door) - Huzaifah (CONTEMPLATE: Jurnal Ilmiah Studi Keislaman, 2023)
Narratives of extremism on the digital stage are increasingly massive, these extremist groups utilize various internet platforms and social media to propagate their ideology more widely. For example, the discourse on jihad, which is interpreted as a verse of war, has become one of the causes that trigger acts of violence, intolerance and dehumanization. To counter the narrative of extremism in society, especially the younger generation (who are very familiar with the digital world), a counter-narrative concept is needed to reduce the extremist narrative with creative conveyances that can reach the younger generation. Habib Ja'far with his more inclusive and multicultural preaching on social media, thoroughly brings religious narratives in moderation, tolerance and countering extremist Islamic narratives. The results of this study indicate that the counter-narrative constructed by Habib Ja'far in the meaning of jihad, first, has an inclusive understanding, second, prioritizes tolerance and moderation in religion, and third is anti-fanaticism.